Otomatisasi Quality Control untuk Mengurangi Lost Time Produksi di PT ISA dengan Metode DMAIC - Apriyani; Devy Juliani; Ainun Nadia; Roberta Heni Anggit Tanisri (Journal of Engineering Environtmental Energy and Science, 2026)
This study aims to reduce lost time in quality control at PT ISA, focusing on part SD-007, which had the highest lost time in 2024. The DMAIC method was applied to systematically improve the process. In the Define stage, long inspection time was identified as the main issue. The Measure stage involved a time study of three operators and 30 samples, showing an average manual inspection time of 740 seconds per part. The Analyze stage revealed that manual and digital measuring tools were time-consuming and prone to operator error. In the Improve stage, the inspection process was automated using a CMM machine with M-COSMOS software, reducing inspection time to 365 seconds per part. A paired sample t-test showed a significant difference before and after improvement (p < 0.05). In the Control stage, SOPs were revised and communicated to QC operators to ensure consistent implementation. The study concludes that inspection automation using DMAIC effectively reduces lost time and improves quality control efficiency at PT ISA.